Busana Kontemporer Dengan Teknik Smock Jepang - Salsabila Sephiani; Dini Yanuarmi (Penerbit dan Percetakan, CV. Picmotiv, 2025)
Contemporary fashion is a style of dress that reflects the development of current or modern fashion, by combining various elements from the past, current trends, to global cultural influences. This clothing has characteristics that can combine traditional elements with modern, in this contemporary fashion makes experiments from forms, sewing techniques and leftover materials as a form of creativity and sustainability prioritizing comfort and practical function. In this work, Riau Malay Songket is used as a local element combined with modern materials. Creating an ethnic and relevant impression in today's fashion. Japanese Smock produces a raised texture from manual manipulation of the fabric applying a heart Smock motif that provides a visual dimension and high aesthetic value. The creation process is carried out through three stages of methods: exploration of ideas and references, design through sketches and moodboards and the embodiment of the work in physical form. The final result in the form of a ready to wear deluxe clothing entitled